Optimization Algorithm for Selecting Compressible Data - E. V. Mozhenkova; T. O. Titovets; A. I. Paramonov (Цифровая трансформация, 2019)
The article deals with the problem of the efficiency of data compression algorithms. The analysis of the effectiveness of the speed characteristics of data compression of the Btrfs file system of the Linux kernel has been performed. An algorithm for optimizing the choice of data for real-time compression is proposed. The described algorithm gives the answer with an acceptable accuracy whether it is necessary to compress the data. This can significantly reduce the use of computing power. The main performance characteristics of the described algorithm are determined.